VD_FINDINFO Décision / 2020 / 116 vom 14. Februar 2020 - VD Tribunal cantonal (2020)
CLASSEMENT DE LA PROCÉDURE, INDEMNITÉEN GÉNÉRAL, FRAISEN GÉNÉRAL, VOLDROIT PÉNAL | 139 CP, 319 CPP (CH), 426 al. 2 CPP (CH), 433 al. 1 CPP(CH)